Validity of Science Process Skills Instrument in E-Modul Guided Inquiry Integration of Tapai Ketan Ethnoscience - Aljunaedi, Aljunaedi; Harlita, Harlita; Yamtinah, Sri (PAEDAGOGIA, 2025)
The development of the Independent Curriculum demands contextual and meaningful learning, especially in science subjects that emphasize science process skills (KPS). The integration of ethnoscience in science learning is a potential solution to link science with local culture, as seen in the process of making sticky rice tapai, which incorporates elements of biotechnology and local wisdom. This study aims to develop and test the validity of the KPS instrument based on guided inquiry e-modules integrated with ethnoscience in biotechnology materials. The method used was Research and Development (R&D), with the ADDIE development model simplified into three stages: analysis, design, and development. The instrument was validated by seven experts using the Aiken index to assess the suitability of content, constructs, and language. The validation results showed that all questions had an Aiken index value ≥ 0.76, indicating high validity. Furthermore, the instrument was tested on 60 students to analyze reliability, difficulty level, and discrimination power. The empirical test results showed that the instrument had high reliability and met the criteria for question quality. Thus, this instrument was declared valid and feasible for use in measuring students' science process skills within the context of ethnoscience-based science learning and guided inquiry. This study supports the development of learning media that are not only scientifically profound but also rooted in local cultural values.